SYMBOLIC INTERACTION PATTERNS BETWEEN FANS AND K-POP BOYGROUP NCT IN LYSN APP - Rahma, Nadine Aulia; Winata, Muhammad Danu (The Commercium, 2024)
The development of Korean culture, especially K-Pop that has entered Indonesia has increased rapidly in recent years. One of the popular K-Pop groups in Indonesia is NCT, which is one of the boy groups under SM Entertainment. The development of K-Pop that goes hand in hand with technological developments creates various platforms that support the interaction experience between fans and their idols. LYSN application is one of the platforms with this function that allows fans to be able to interact with their idols which is made to resemble a private chat application so that fans will feel a different experience. This research uses a qualitative method with a phenomenological approach. The object of this research is the symbolic interaction that occurs in the LYSN application, with the research subject being NCT fans (NCTzen) who subscribe to LYSN for 2 months or more. The results showed that the symbolic interactions that occur in the LYSN application provide a deep meaning for fans who subscribe, the meaning forms various interpretations which then affect what actions will be taken.